The Effectiveness of Inclusive Education and Child Protection Training on Understanding Inclusive Education Subject Matter - Munawir Yusuf; Salim Choiri; Gunarhadi Gunarhadi (Department of Special Education, 2018)
The main objective of this study is to examine the effectiveness of inclusive education trainning for the teacher using of the main learning material (BPU) of Inculsive Education and The Child Protection as compulsory course in Faculty of Teacher Training and Education, Sebelas Maret University. The quantitative research method was adopted for this study using twenty five valid item in pre-post questionnaires completed by twenty five teacher in Faculty of Teacher Trainning and Education, Sebelas Maret University. The data were collected using instrument that measures the concept of inclusive education and child protection as pre-post questionnaires. The data collected were analyzed using quantitative analysis through Paired sample t-test to find the difference in distance run between pre and post test. Based on the results, there was difference between mean score of pretest and posttest (17,32-19,84). The paired sample t-test was used to determine whether there was a statistically significant difference in distance run between the two trials. The paired sampel t-test showed that p-value is lower than α-value (0,000<0,05). The findings indicates that trainning for teacher using the main learning material (BPU) of Inculsive Education and The Child Protection is effective to enhance the comprehension in understanding inclusive education course as compulsory course in Faculty of Teacher Training and Education, Sebelas Maret University